Kose- und Spitznamen als Spiegel sozialer Stereotype - Stocker, Christa (My University, 2004)
Pet names and nicknames are not arbitrarily chosen, they rather verbalize habits and characteristics of a person. Thus, they do not only fix references, but also categorize people. They assign people to social groups and characterize them. Not all aspects and names seem to be suitable for naming, however. There is a limited range of semantic fields that are used for naming. Only words of some special fields are used as pet- and nicknames, while others are not, indicating that there exist customs of naming. Habitual pet- and nicknames attribute prototypical characteristics to a person and thereby stylize it, as these names depend on the beliefs, dispositions, and stereotypes of a social stratum. They reflect and preserve social stereotypes and therefore can be taken as mirrors on social stereotypes as a study of girls' books of the 19th century shows.